KEDUDUKAN KREDITOR SEPARATIS DALAM KEPAILITAN SETELAH PUTUSAN MAHKAMAH KONSTITUSI NOMOR 67/PUU-XI/2013 DIKAITKAN DENGAN UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Rasyid Anbari; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The law guarantees granting separatist as most creditors creditors precedence against collateral objects (droit de preference), this rule adopted by the Bankruptcy Act and the PKPU entitles the creditor to execute his right as if the separatists do not occur bankruptcy and putting the creditor have the right preceded the separatists against the collateral objects. The Constitutional Court issued a Ruling Number 67/PUU-XII-2013 which interprets Article 95 employment law, thus placing laborers wage positions become higher than the separatist's creditors. The position of creditors became unclear after the separatist conflict between the Bankruptcy Act and the Constitutional Court's ruling against PKPU Number 67/PUU-XII-2013, this becomes an interesting study because it potentially gives rise to legal uncertainty especially in the practice of their implementation. The purpose of writing this thesis, namely; First, the position of creditors in bankruptcy separatists after the ruling of the Constitutional Court the number 67/PUU-XI/2013, second, the rule of law guarantees associated with the Kontitusi Court ruling Number 67/PUU-XI/2013 against the separatist's creditors.This type of research can be classified in types of juridical normative research, because in this study the authors use the study material libraries such as official documents, books for research, in this study, the data source used, the primary data, secondary data and data tertier a data-collecting technique in this study with the method of the study of librarianship or documentary studies.From the results of this research can be concluded, the first position of the separatist's creditors in bankruptcy after the ruling of the Constitutional Court the number 67/PUU-XI/2013 raises legal uncertainty in the process of bankruptcy because creditors rights recognized separatist forestalled in the Insolvency law. The Labour Bill and the tax bill is higher than what his creditors the creditors only in terms of separatist rebels of objects so that the right does not implement a guarantee fall within boedel bankrupt, if the creditor uses the separatists the right according to article 55 of the Act Bankruptcy then still get first position for the first payment. Second, the rule of law guarantees associated with the ruling of the Constitutional Court the number 67/PUU-XI/2013 will be contradictory because the separatists as the holder's creditors seeking material guarantees that the basic law has protected the guarantee that is the basis of droit de preference which gives precedence to position against the collateral objects. This dispute raises legal uncertainty related judicial guarantees in insolvency proceedings, the warranty becomes no longer meaningful because the intent of the holding of judicial guarantees is to give preference to the holder of the guaranteein payment of the debts of the debitor. Keywords: Breakaway-Creditors Bankruptcy-Wages Of Laborers